The Effect of Implementing Good Corporate Governance (GCG) on the Financial Performance of Islamic Banks in Indonesia - Khairiah, Nadyatul; Inayah, Nailul (Accounting and Sustainability, 2023)
The implementation of Good Corporate Governance (GCG) in Indonesia's Islamic banking sector is an important step to ensure transparency, accountability and fairness in the operations of financial institutions. As an integral part of the financial system, Islamic Banks not only provide services in accordance with Islamic economic principles but are also expected to implement good corporate practices to maintain the sustainability and reliability of the financial system.Corporate governance in the banking sector gained attention after the 1997 financial crisis, with the establishment of the National Committee on Governance Policy (KNKG) in 1999. Analysis of previous research results shows variations in the effect of GCG implementation on the financial performance of Islamic banks. Some studies found a significant positive impact, while others showed negative or insignificant results. Variations in results are also seen in performance indicators such as CAR, NPF, ROA, and ROE, reflecting the complexity of the relationship between GCG and aspects of financial performance. Therefore, deeper contextual understanding and improved effectiveness of GCG implementation are needed to understand and maximize its impact amidst increasingly complex financial market dynamics.